Understanding Impacts of Security Check on Passenger Flow in a Metro Station and Improving Measures: A Case Study in Guangzhou, China - Heng Yu; Yimin Wang; Feng Wang; Peiyun Qiu (Journal of Advanced Transportation)
In order to ensure the safety of passengers using metro stations and staff working at them, some cities choose to set security checks at the entrances of metro stations. There is no doubt that security check can help keep dangerous objects out of a metro station. However, the security check can also slow down the entering speed of passenger flow and lead to congestions that may affect passengers’ travel plans. How security check will impact the passenger flow and how to reduce the impact are questions that need to be addressed. In this study, metro station models were constructed using the building structure and passenger flow data of a realistic metro station in Guangzhou, China. By using the AnyLogic simulation software, the traffic characteristics of passenger flow under the scenarios with and without a security check were compared and discussed. The congested areas in the station hall and possible causes were analyzed. In addition, possible improving measures such as adding security check machines and ticket vending machines were also modeled to test their effectiveness on reducing the congestion in the station. Results show that when security checks are set at each entrance of the station being studied, the flow rate of passengers entering the gate machine could be decreased by 49.4%~83.3%, which can cause serious congestion at the entrance during rush hours. By adding security check machines and ticket vending machines at the entrances with high passenger traffic demands, the congestion near these entrances could be greatly reduced.